Knowledge Mobilization of Anti-vaccine Movement in Social Media - Widyaningrum, Novi; Trisnantoro, Laksono (PCD Journal, 2022)
This study observes social movement in the digitalized era, especially on how the actor of anti-vaccine movement connected as well as spread and formed the knowledge in the social media. This study is essential to be further explored to enrich the theories of anti-vaccine in the digital era. The case to be studied here is the anti-vaccine movement on Facebook, which has developed in the context of the socio-politics of the Indonesian people in 2018-2019. Using Content Analysis as the method, this study finds that the Anti-vaccine Movement in Indonesia rejected the vaccine program by attacking the knowledge hegemony created by medical institutions and the government. It has formed new knowledge by issuing a counter toward the medical discourse. The argument centered on moral anger and structural repression by government agencies, worldwide institutions, pharmacy industries, and media and showed strong logic based on religious belief. This fact indicates that social media plays a role in spreading anti-vaccine ideas and gives way for the movement to develop and to have a dynamic network that can survive for a long of time. By mobilizing knowledge through a social movement in the digitalized world, the anti-vaccine movement in Indonesia has a broader network. It has the potential to influence the success of the government program.